Investigating the relationship between work incidents and musculoskeletal disorders in motorcycle technician workshops: a cross-sectional analysis - Fikrihadi Kurnia; I Made Suartika (Universitas Mercu Buana, 2025)
Workplace hazards and incidents pose significant risks in the automotive industry, necessitating meticulous risk assessment and management. This cross-sectional study was designed to examine the prevalence of work-related injuries and musculoskeletal disorders (MSDs) among motorcycle technicians in workshops situated within Lombok Island, West Nusa Tenggara, Indonesia. A sample of 105 male participants was recruited for the study. Findings revealed that the majority of workers were aged between 20-30 years (67.6%), possessed vocational high school education (61%), were married (55.2%), had 1-10 years of work experience (83.8%), were smokers (58.1%), and abstained from alcohol consumption (83.8%). Workplace incidents predominantly comprised minor injuries (93.3%), with the hands being the most frequently affected body part (65.5%). Additionally, lower back MSDs were prevalent (74.3%) and significantly correlated with workplace incidents. The study concludes that upper extremities were the most commonly affected body part in both incidents and MSDs. These findings emphasize the value of prioritizing workplace safety and implementing preventative strategies to mitigate MSDs in motorcycle workshops, ultimately fostering worker well-being and enhancing workshop productivity.